Precision nutrient management Innovative technology for enhancing income in farming system - Kumar, Sandeep; Hasanain, Mohammad; Singh, Rajiv Kumar; Rathore, Sanjay Singh (Indian Farming, 2025)
India is one of the largest consumers of fertilizers in the world and also has 2nd highest arable lands. This is required to ensure food and nutritional security of huge population. But losses of fertilizer nutrients due to faulty application is a serious concern. The recovery efficiency of nutrients from fertilizers is about 30-50%, 15-20%, 50-80%, 1-5 and 5-12% for N, P, K, micronutrients and secondary nutrients, respectively. This poor nutrient use efficiency not only leads to a decrease in crop yield but also increases cultivation costs, environmental pollution and nutrient imbalance. The agronomic efficiency of the nutrient has also been decreasing every year since the introduction of the Green Revolution technologies. This low fertilizer use efficiency and indiscriminate use of fertilizers have increased the import of chemical fertilizers, which is also a major problem for the Indian economy. Therefore, there is an urgent need to explore or popularize the innovative technology for precise nutrient management. So far, various tools and technologies have been tested in the research center as well as in the farmers field such as: Green Seeker, Leaf Color Map, Soil Plant Analysis Development (SPAD), Nutrient Expert, Crop Manager, Site Specific Nutrient Management and Nutrient Recommendation based soil health card, nutrient indexing or soil test plant response. Precision nutrient management technologies have been shown to improve grain yield by 6-15%, net returns by 7-25%, nitrogen saving by 5-25 kg/ha and nutrient use efficiency also by 5-15%, which is beneficial for agriculture prosperity and increased income of the farmers of the country.